A Spy took a bite to get the diagnosis right: the benefit of SpyGlass technology in the diagnosis of autoimmune pancreatitis evading traditional diagnostic methods - Dianne Grunes; Adam Matthew Parker; David Schaefer; Amor Royer; Hardik Sonani; Sarah Camille Glover (BMJ Open Gastroenterology)
Autoimmune pancreatitis (AIP) is a rare form of chronic pancreatitis that is often overlooked and is usually characterised clinically by frequent presentations with obstructive jaundice. Serum IgG4 testing as a means to ‘rule out’ IgG4-related disease may not be as helpful as initially thought and may lead to a missed diagnosis if suspicion is low. We present a patient with a years long history of recurrent pancreatitis ultimately found to have AIP after undergoing evaluation with a relatively new technology, SpyGlass, which allows for direct cholangioscopy and enabled us to make the correct diagnosis.